The Delegation of the Bohemian King-Elector to the Election of the New Roman King in Frankfurt am Main, 1745 - Kubeš, Jiří (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2023)
It may seem that we know a lot about the elections and coronations of Roman kings and emperors in the seventeenth and eighteenth centuries, and this also applies to the one of 1745, when Francis I Stephen became emperor. However, very little attention has been paid to the electoral delegations, their tasks, and their role in the pre-election negotiations. This article will therefore analyse the instructions issued by Queen Maria Theresa of Bohemia, who did not personally come to Frankfurt am Main for the election, to her diplomats. The analysis will then be supplemented by additional sources from the National Archives in Prague, where the reports of the delegation and other sources have been preserved. The election of 1745 is thoroughly compared with the elections of 1657–58 (Leopold I), 1711 (Charles VI), and 1742 (Charles VII). The author shows who made up the Bohemian delegation and how some of these diplomats’ tasks changed over time. Although the delegation of three noblemen – Counts Wurmbrand and Khevehüller, and Baron Hilleprand – had mainly ceremonial tasks, its role was also crucial in the actual negotiations, both on the very day of the election, then when it represented the Queen in the cathedral, and finally in conclave vote and when it was given other tasks (such as organising the celebratory banquet, illuminating the houses, etc.). It is evident that the delegation helped Queen Maria Theresa and her family regain possession of the imperial title.